Women's Sense of Security at Work: Maternal Role and Fear of An Uncertain Future - Marssel Michael Sengkey; Tellma Monna Tiwa (Jurnal Psikologi, 2020)
Women's participation in the work space is needed, however, the workplace's ability to provide a sense of security for women is still not optimal, especially when pregnant or breastfeeding. This study aimed to explore the construction of female workers' sense of security when carrying out their maternity roles. This study used qualitative approach with thematic analysis methods to construct a sense of safety variable. The respondents were eight women who cleaned and skinned fish in fish processing companies. The results showed that female workers have concerns and fears when carrying out their maternal roles (pregnancy, childbirth, and breastfeeding), which hinders the formation of a sense of security work. Little or less sense of security felt by female workers comes from three major themes, namely physical demands at work, a work environment that is not conducive and uncertainty in work relationships that raise concerns in carrying out their maternal roles. Security for working women is not only determined by physical security, but also by the degree of certainty or uncertainty in the work relationship.